Formal Learning Still Dominates: A Qualitative Coding Analysis of Civil Servant Competence Development in Medan City Government - Adrian Saleh; Tengku Irmayani; Husni Thamrin (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study analyzed the methods used to develop the competence of civil servants (Aparatur Sipil Negara/ASN) at the Medan City Personnel and Human Resources Development Agency (BKPSDM) and their relationship to the performance of the Medan City Government. A descriptive qualitative approach was used, with data drawn from in-depth interviews with the Head of BKPSDM, the Head of the HR Development Division, eight BKPSDM staff, twenty ASN training participants, and three academics, supplemented by field observation and document review, and analyzed through inductive coding. The findings showed that competence development remains dominated by classroom training (22% of implementation codes), followed by blended learning and training administration (15% each), while coaching, mentoring, and digital learning are present but not yet systematically embedded. The intervention was perceived as effective mainly where training content matched job needs and participants stayed engaged, but post-training evaluation and monitoring, budget constraints, and partial misalignment between training content and position requirements remained persistent constraints. Organizational supportparticularly peer learning and digitalizationhelped offset these limitations. The study concludes that competence development at BKPSDM Kota Medan is shifting gradually from a purely classroom-based model toward a more blended and digitally supported one, and recommends strengthening post-training evaluation, position-based training design, and organizational learning culture to translate competence gains into sustained government performance.